2017
DOI: 10.1515/optof-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Optofluidics for handling and analysis of single living cells

Abstract: Abstract:Optofluidics is a field with important applications in areas such as biotechnology, chemical synthesis and analytical chemistry. Optofluidic devices combine optical elements into microfluidic devices in ways that increase portability and sensitivity of analysis for diagnostic or screening purposes .In fact in these devices fluids give fine adaptability, mobility and accessibility to nanoscale photonic devices which otherwise could not be realized using conventional devices. This review describes sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…However, it can as yet not be used as the only technique for any kind of diagnostics, and is either combined with other tests to create assays [63,66], or needs massive automation and robotics [156] or artificial intelligence to arrive at a diagnosis [156,157]. The usage of optical traps for single cell diagnosis is mostly limited to optical stretching [158], cell-sorting [66,154,[159][160][161][162], and measuring of refractive indices [140,[162][163][164]. Especially in combination with automatization, optical traps for single cell diagnostics have a great potential, but currently it is among the more expensive and less-performing technologies.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, it can as yet not be used as the only technique for any kind of diagnostics, and is either combined with other tests to create assays [63,66], or needs massive automation and robotics [156] or artificial intelligence to arrive at a diagnosis [156,157]. The usage of optical traps for single cell diagnosis is mostly limited to optical stretching [158], cell-sorting [66,154,[159][160][161][162], and measuring of refractive indices [140,[162][163][164]. Especially in combination with automatization, optical traps for single cell diagnostics have a great potential, but currently it is among the more expensive and less-performing technologies.…”
Section: Figurementioning
confidence: 99%
“…Works intracellularly Relies on differences in refractive indices (e.g. DNA-rich parts like the nucleus) The application of optical tweezers for the handling of single cells and for diagnostics on the single cell level has recently been discussed a lot [138,141,154,155]. However, it can as yet not be used as the only technique for any kind of diagnostics, and is either combined with other tests to create assays [63,66], or needs massive automation and robotics [156] or artificial intelligence to arrive at a diagnosis [156,157].…”
Section: Contact-free Micromanipulation Needs Electricity and Lasers mentioning
confidence: 99%
“…Localized surface plasmon (LSP) and surface plasmon polariton (SPP) have been developed to manipulate fluid convection, living cells, DNA, and proteins. [9][10][11][12][13] For example, the photothermal effect caused by LSPs of Au NPs' array in optofluidics was investigated by Miao et al [12] Such LSP energy-induced optofluidic mixing could obtain high optical-to-thermal energy conversion efficiency. Min et al showed the optofluidic trapping and manipulation of metallic particles by the excitation of SPP on a thin layer of the gold film.…”
mentioning
confidence: 99%